VERTICALIZAÇÃO NAS EDIFICAÇÕES COSTEIRAS E SOMBREAMENTO NAS PRAIAS DAS FLECHAS E ICARAÍ - Souza, Juliana; Rosa, Letícia; Lomardo, Louise (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The high-income residents of Niterói are concentrated in a highly valued part of the city: the coastal neighborhoods. Due to this valuation, the vertical development process becomes stronger and stronger, particularly on Flechas Beach and Icaraí Beach. There are many high standard buildings on these places. These constructions may project shade on the sand and even in the sea, disturbing the local use of the beaches, their microclimate and ecosystem. So, this study aims to analyze the shading caused by coastal buildings using descriptive geometry's calculations and a virtual simulator of shadows. At the same time, the objective is to contribute to the discussion of the vertical development in coasts and impacts that the permissiveness legislative and supervisory can generate in the urban space.